Expert consensus-driven refinement of NExGEN prompt generator and AI Chatbot frameworks for personalized athletic planning / Adam Irman Roslin ... [et al.]. - Roslin, Adam Irman; Mohd Dan, Azwa Suraya; Sazali, Razif; Md Yusoff, Yusandra; Zulqarnain, Muhammad; Haziq, Amrun; Linoby, Adam (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study refines the NExGEN Prompt Generator–ChatGPT Framework for personalized training and nutrition planning in team sport athletes using the Fuzzy Delphi method. It addresses the limitations of current costly and time-intensive personalized health solutions, focusing on scalable, technology-driven alternatives to improve accessibility and effectiveness [1]. This study refined the NExGEN Prompt Generator–ChatGPT Framework through expert input using the Fuzzy Delphi Method. A purposive sample of 21 experts from nutrition, exercise, medicine, psychology, and AI evaluated personalized planning criteria via surveys. Data were analyzed using Triangular Fuzzy Numbers and defuzzification, ensuring consensus on effectiveness metrics. Expert feedback, collected through Likert scales and open-ended responses, informed iterative framework improvements.